Philosophical Numeracy Literacy in Sundanese Local Wisdom - Sudaryat, Yayat; Suherman, Agus; Widyastuti, Temmy (International Journal of Multidisciplinary Sciences, 2025)
The old Sundanese people already had numeracy literacy or the ability to understand and use numbers. This is evident in some ancient Sundanese manuscripts. This study aims to describe the use of numbers philosophically in the life of the old Sundanese people. In the study, a qualitative approach with a descriptive method was used. Data were collected by bibliographic study techniques. Data sources are ancient Sundanese manuscripts Sanghyang Siksakandang Karesian (1518 AD) and several Sundanese culture books. The data is processed by immediate constituent analysis techniques. To carry out the philosophical interpretation of numeracy literacy used hermeneutic analysis techniques. The results of the study found five paradigms of numeracy literacy, namely numeracy paradigm- (two, three, four, five, and ten). These figures are used in philosophical expressions as Sundanese local wisdom. Philosophical values are related to character, social life, knowledge, education, leadership, and religion.